Pengaruh Kualitas Pelayanan Kesehatan dan Harga Premi Asuransi Terhadap Kepuasan Pasien Rawat Jalan Peserta Badan Penyelenggara Jaminan Sosial Kesehatan - Mutiara Islam Asir; Kadunci *; Ni Made Widi (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2022)
This study aims to determine and analyze the partial and simultaneous effect of the quality of health services and the price of insurance premiums on the satisfaction of BPJS Health participants at the Trimedika Clinic. In addition, this research is expected to be a consideration for the clinic and the BPJS to improve and maintain the existing quality. This study includes causal associative research with a quantitative approach and the number of samples taken as many as 97 respondents determined by non-probability sampling technique with purposive sampling method. Data collection was carried out using literature studies and distributing questionnaires. Instrument testing using validity and reliability tests. Meanwhile, the data analysis method used classical assumption test and hypothesis testing. This study was tested using SPSS 22. The results of this study indicate that: (a) Service quality(X1) and insurance premium prices(X2) have a significant effect of 44.3%, (b) The coefficient of determination is 0.443. This means that the dependent variable is influenced by the independent variable by 44.3% and the other 55.7% is influenced by other variables outside the variables used in this study. Based on the results of this study, the quality of service and the price of insurance premiums have an influence on the satisfaction of BPJS participants at the Trimedika Clinic, Bekasi